Proton Pump Inhibitor Therapy Does Not Affect Prognosis of Cirrhosis Patients With Acute Decompensation and Acute-on-Chronic Liver Failure: A Single-Center Prospective Study - Sun, Shanshan; Ye, Wenyi; Zhao, Ruihong; Hu, Jianhua; Zhang, Xuan; Yang, Meifang; Zhao, Hong; Sheng, Jifang (Frontiers in Medicine, 2021)
Background: The aim of this study was to investigate the impact of proton pump inhibitor (PPI) therapy on complications and prognosis in cirrhosis patients with and without acute-on-chronic liver failure (ACLF). Materials and methods: Cirrhosis patients with acute decompensation (AD; n = 489) admitted in our center were enrolled in this prospective observational cohort study. According to treatment received, patients were identified as users or non-users of PPI. Clinical and laboratory data, complications during hospitalization, and overall survival were recorded in all patients. Results: Of the 489 patients, 299 (61.1%) received PPI therapy. Logistic regression analysis showed that age, albumin, history of previous HE and CLIF-SOFA score were independent risk factors for HE in patients with decompensated cirrhosis (odds ratio [OR] =1.07, 95% confidence interval [CI]: 1.03-1.12, p=0.001; odds ratio [OR] =1.13, 95% confidence interval [CI]: 1.04-1.24, p=0.006; odds ratio [OR] = 242.52, 95% confidence interval [CI]: 40.17-1464.11, p < 0.001; and OR =2.89, 95% CI: 2.11-3.96, p < 0.001, respectively]. Previous severe liver injury and previous bacterial infections were independent risk factors for spontaneous bacterial peritonitis (SBP) in patients with decompensated cirrhosis (OR =3.43, 95% CI: 1.16-10.17, p = 0.026 and OR = 6.47, 95%CI: 2.29-18.29; p <0.001, respectively). Multivariate Cox proportional hazard model analysis showed that the type and dose of the PPI used were not related to 28-day and 90-day mortality in cirrhosis patients with AD or ACLF. Conclusions: PPI use does not appear to increase mortality or the risk of HE and SBP in hospitalized cirrhosis patients with and without ACLF.